Evaluasi Pengelolaan Keuangan Dana Desa Pada Masa Covid-19 Di Desa Pandanlandung Kabupaten Malang - Risnaningsih Risnaningsih; Ahmad Mukofi; Filaria Hendrani (Department of Accounting, Faculty of Economics & Business, 2022)
This study aims to evaluate how the Financial Management of Village Funds During the Covid-19 Period in Pandanlandung Village, Wagir District, Malang Regency using qualitative research methods, with Village Head informants and Pandanlandung Village Government officials whose research focus is planning, implementation, administration, reporting and accountability. The data collection used is by interview, document and observation. The results of research conducted by researchers indicate that the financial management of the Pandanlandung Village Government is in accordance with Permendagri Number 113 of 2014 namely planning, implementation, administration, reporting, and accountability which are very effective so that they are sufficient and beneficial for the community.